GFP Scaffold-Based Engineering for the Production of Unbranched Very Long Chain Fatty Acids in Escherichia coli With Oleic Acid and Cerulenin Supplementation - Kassab, Elias; Mehlmer, Norbert; Brueck, Thomas (Frontiers in Bioengineering and Biotechnology, 2019)
Currently, very long chain fatty acids (VLCFAs) for oleochemical, pharmaceutical, cosmetic or food applications are extracted from plant or marine organism resources, which is associated with a negative environmental impact. Therefore, there is an industrial demand to develop sustainable, microbial resources. Due to its ease of genetic modification and well characterized metabolism, Escherichia coli has established itself as a model organism to study and tailor microbial fatty acid biosynthesis using a concerted genetic engineering approach. In this study, we systematically implemented a plant-derived (Arabidopsis thaliana) enzymatic cascade in Escherichia coli to enable unbranched VLCFA biosynthesis. The four Arabidopsis thaliana membrane-bound VLCFA enzymes were expressed using a synthetic expression cassette. To facilitate enzyme solubilization and interaction of the synthetic VLCFA synthase complex, we applied a self-assembly GFP scaffold. In order to initiate VLCFA biosynthesis, external oleic acid and cerulenin were supplemented to cultures. In this context, we detected the generation of arachidic (20:0), cis-11-eicosenoic (20:1) and cis-13-eicosenoic acid (20:1).